REALITY OF SMALL INDUSTRIAL ENTERPRISES IN IRAQ FOR THE PERIOD FROM 2014-2024 (FROM AN ACCOUNTING PERSPECTIVE) - Ammar Mohammed Hussein; Haitham Mohsin Kareem; Omar Hamad Nsaif (Scholar Express Journals, 2025)
This research aims to shed light on the situation of small industrial enterprises in Iraq over a long period, particularly during the period when ISIS controlled large parts of the country, as well as during the COVID-19 pandemic. In order to understand how security events and the pandemic have affected these enterprises in terms of access to financial liquidity and the ability to continue competing for market share and profitability, it is therefore important to analyze the impact of the pandemic. This is crucial given its global nature. The study will cover a period of approximately 10 years, from 2014 to 2024. The study used secondary data obtained from the Central Statistical Organization to determine how security events and the pandemic have affected small industrial enterprises, their accounting implications, and the period following them. A questionnaire was conducted to collect primary data from small industrial enterprises. The purpose was to understand the perspectives of managers and owners regarding the continuity of their businesses during the pandemic. Descriptive analysis was used to achieve this objective. According to the results of a survey of 282 small industrial establishments, a large number of owners and managers are uncertain about the future of their businesses and may not be able to continue operating under similar conditions in the future. The researchers relied on self-financing to complete this study.
Keywords: Small Industrial Enterprises; COVID-19; Accounting